MEASURING THE SKILLS OF LEADERSHIP AND INSTRUCTIONAL COACHES FOR SCHOOLS TRANSFORMATION PROGRAMME - Jeffri Idris, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The study aims to determine the levels of coaching skills among the school transformation coaches. They are specially selected mainly to assist school leaders and teachers in transforming the schools and students towards excellence. The objectives of this study are first, to assess the levels of listening and questioning skills, and second, to identify the extent of the related skills being used. There are five listening sub-skills and five questioning sub-skills identified for the purpose of this study. It comprises 43 participants selected from 110 coaches who have been involved since the programme started in 2016. The study uses quantitative and qualitative approaches. The participants are required to carry out a coaching simulation session. Each of them is given 20 minutes to conduct the session and 10 minutes for feedback session. They are assessed by two certified coaches for each session. A checklist form and grading form are used as instruments. There are four levels of competency to identify the participants’ listening and questioning skills known as Ineffective (1), Developing (2), Skilled (3) and Excellent (4). The results of the study find that most of the participants are at the ‘Skilled’ level for both listening and questioning skills. The former was at the Mean level of 3.33 and the latter was at 3.58. Further analyses for listening component skill find that the sub-skill of ‘making conclusion’ is used by most of the participants and the sub-skill of ‘using decision making tools’ is the least used. For questioning skill component, the sub-skill of ‘using appropriate open and closed questions’ is the most used and the sub-skill of ‘creating awareness for decision making improvement’ is the least used. It can be concluded that the participants’ have good skills in listening and questioning for coaching. It is suggested that they need to further develop their skills in helping their coaches to make decision using appropriate tools and for improvement.